Spiritual Strengthening Through Religious Development in Potoan Daja Village, Palengaan Pamekasan - Mukit, Abdul; Arifin, Zainal; Yakin, Nurul; Mubarok, Sabiqul; Iqbal, Moh; Yakin, Ainol; Hidayat, Rizki (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2023)
In today's era, humans are facing increasingly complex life challenges. For that, a strong religious foundation is needed. The research aims to strengthen religion through the congregational prayer movement in Potoan Daja Village, Palengaan Pamekasan. Religion is a treatise conveyed by God to the Prophet as a guide for humans and perfect laws to be used for humans in carrying out real life procedures and regulating relationships with responsibility to Allah, to society and the natural surroundings. The methodology used is mixed methods, namely a combination of literature and field studies. Where the literature study is carried out to formulate the theory, while field studies are carried out through direct observation of the location of the object of study. The findings of this study are that the Religious Guidance Through the Congregational Prayer Movement conducted in Potoan Daja Village is highly appreciated by the community and directly increases religious and religious awareness. Activities to Strengthen Religious Development through the Congregational Prayer Movement in Potoan Daja Village, Palengaan Pamekasan have succeeded in fostering a new prayer room at the residence of Mr. Muhammad Bhere' Sabe with two male and female shafs through the preparation of the main and supporting programs using the lecture and story method.